IMPLEMENTATION OF PEDAGOGICAL CONTENT KNOWLEDGE WITH MULTIMEDIA ON RECTILINEAR MOTION TOPICS - Effendy, Suhardi; Ellianawati, Ellianawati (Universitas Negeri Semarang, 2019)
Pedagogical content knowledge is a combination of understanding knowledge material (content knowledge) and ways of educating (pedagogical knowledge). The purpose of this study is to improve student learning outcomes and interests through the implementation of multimedia assisted pedagogical content knowledge. The research method used is control group pretest-posttest design. Data collection was done by test and questionnaire. Data analysis using t test and gain test. The results showed that there was an increase in learning outcomes by the implementation of pedagogical content knowledge (PCK) with t count > t table and N-gain score of student learning outcomes of 0.60. Questionnaire results show the high interest of students in learning by using multimedia of Rectilinear motion.